2006
DOI: 10.2340/00015555-0145
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Knowledge Among Psoriasis Patients Can Represent a Barrier to Participation in Decision-making

Abstract: Patient participation in treatment decisions can have positive effects on patient satisfaction, compliance and health outcomes. The objectives of this study were to examine attitudes of psoriasis patients regarding participation in treatment decisions and to evaluate the effect of a decision-aid for discussing treatment options. A "quasi experiment" was conducted in a large dermatological hospital in Italy: a questionnaire evaluating the decision-making process and treatment knowledge was self-completed by 231… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 30 publications
4
53
1
1
Order By: Relevance
“…Poor adherence to treatment advice for psoriasis represents a major challenge to health care professionals [5]. It has been demonstrated that insufficient knowledge among patients with psoriasis can represent a barrier to therapy acceptance and adherence [6]. Indeed, effective communication between doctor and patient is crucial in the management of psoriasis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Poor adherence to treatment advice for psoriasis represents a major challenge to health care professionals [5]. It has been demonstrated that insufficient knowledge among patients with psoriasis can represent a barrier to therapy acceptance and adherence [6]. Indeed, effective communication between doctor and patient is crucial in the management of psoriasis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients should therefore be encouraged to disclose this information either formally via the use of standardized tools such as the DLQI or informally via a discussion. With regards to communication on treatment options, physicians may overestimate their patients' disease education [13,14,21]. Particularly, psoriasis patients have previously expressed a desire for more information from their dermatologists [16].…”
Section: Discussionmentioning
confidence: 99%
“…Such strategies emphasize active involvement by the patient and two-way communication leading to physician -patient consensus regarding the preferred treatment approach [12,14]. In relation to this, alignment between physicians and their patients is emerging as an important concept to ensure the successful implementation of a treatment plan as well as optimal outcomes [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Grilli [14] reports on a consensus conference, involving all relevant stakeholders (professional societies, patients and consumer associations, epidemiologists, health economists and administrators) aiming to develop recommendations for breast cancer follow-up. Renzi et al [15] conducted a ''quasi-experiment'' evaluating the effect of a decision-aid for discussing treatment options with psoriasis patients. Among the observational studies, Goss et al [16] have shown a low frequency of patient expressions of opinions and questions immediately before and after general practitioners (GPs) gave information, and a lack of facilitating questions by GPs, indicating a limited degree of patient involvement in the consultation.…”
Section: Examples Of Published Research Projectsmentioning
confidence: 99%